Membaca Persoalan Hijab dan Otonomi Perempuan Melalui Epistemology Ignorance - Pertiwi, Saniyah; Asnawi, Naupal (Paradigma: Jurnal Kajian Budaya, 2022)
Apart from its religious values, the hijab has currently developed into a lifestyle. The issue concerning the hijab in Indonesia has evolved over time with a fascinating complexity that is worth to be examined. The Indonesian people who have the habit of questioning the decision to wear or not to wear the hijab illustrates that the choice of Indonesian women is not considered as a personal matter. This research will discuss how the phenomenon of “questioning the decision to wear or not wear the hijab” is based on the epistemology of ignorance, which investigates and explains how ignorance is formed and preserved in this phenomenon. The revelation of the women’s complex experiences concerning their hijab is part of the epistemology of ignorance. This research uses a literature study method to obtain sources and present data, followed by a critical reflection method to explore and reflect on ignorance in the phenomenon under study. This article concludes that interfering in women’s decisions to wear or not to wear the hijab is a form of ignoring women’s subjective experiences and women’s autonomy because it creates misunderstandings and violates human rights.